Additive Manufactured Waveguide for E-Band Using Ceramic Materials - Florian Hubert; Tobias Bader; Larissa Wahl; Andreas Hofmann; Konstantin Lomakin; Mark Sippel; Nahum Travitzky; Gerald Gold (Applied Sciences, 2021)
Ceramic materials are chemical- and temperature-resistant and, therefore, enable novel application fields ranging from automotive to aerospace. With this in mind, this contribution focuses on developing an additive manufacturing approach for 3D-printed waveguides made of ceramic materials. In particular, a special design approach for ceramic waveguides, which introduces non-radiating slots into the waveguides sidewalls, and a customized metallization process, are presented. The developed process allows for using conventional stereolithographic desktop-grade 3D-printers. The proposed approach has, therefore, benefits such as low-cost fabrication, moderate handling effort and independence of the concrete waveguide geometry. The performance of a manufactured ceramic WR12 waveguide is compared to a commercial waveguide and a conventionally printed counterpart. For that reason, relevant properties, such as surface roughness and waveguide geometry, are characterized. Parsing the electrical measurements, the ceramic waveguide specimen features an attenuation coefficient of 30–60 dB/m within the E-Band. The measured attenuation coefficient is 200% and 300% higher compared to the epoxy resin and the commercial waveguide and is attributed to the increased surface roughness of the ceramic substrate.